Impact of Logistics Training on Freight Transportation Companies in Bogotá - Pachón Pedraza, Hugo Almeiro; Alfonso Corredor, Breed Yeet; Sánchez Martelo, Carlos Augusto; Cadena Chala, Martha Cecilia (Springer, 2024)
Land cargo transportation companies have been growing, due to the increases in cargo volumes generated in the city, in the same way there are other relevant variables such as the expansion of population growth, the design and creation of new highways, Los Changes in the territorial planning plan, among others, have required these companies to have greater specialization in logistics processes, but this has been able to be improved, hand in hand with the use of technological and digital tools, which facilitate the process and to provide reliable and timely information to its customers. The foregoing is a demand from these companies to have personnel that demonstrate better skills, competencies and attitudes in the control and administration of internal logistics processes, which is reflected in greater efficiency in their daily operational and administrative performance. The purpose of this article is to show the impact of training and education in the logistics area in cargo transport companies in the city of Bogotá and the incidence of human talent in the industrial and logistics growth of these companies, due to the training academic that said personnel must have. This is achieved through the analysis and logistic performance of cargo transportation companies in Bogotá, and how their productivity improves significantly with the academic training of the personnel who work in them.
Keywords: logistics processes; management; smart technologies; Scopus(2)